New Syllabus Governement for Senior Seconndary Schools Book Three - A E C Ogunna et al (Evans Brothers (Nigeria Publishers) Limited, 1991)
This book is a seris of three books specially written for students of government at Senior Secondary levels based on the Federal Ministry of Education New Syllabus for Senior Secondary Schools.
Keywords: Political Science- Study and Teaching- Nigeria (Secondary)